Research of thermal conductivity of the condensed mass of the whole waste tires and determination of their optimum arrangement in the pyrolysis reactor - Ryzhkov, Serhiy; Rudyuk, Nikolay; Markina, Liudmyla (Eastern-European Journal of Enterprise Technologies, 2016)
The theoretical study of the total thermal conductivity of three selected anisotropic structures of binary cells proved that the asymmetric arrangement of whole tires in the pyrolysis reactor, which provides the maximum thermal conductivity of the mass of whole tires in the reactor is the closest to realistic conditions. With the asymmetrical arrangement of tires in the reactor, in the process of consolidation, bead rings overlap, creating a metal lattice with thermal conductivity of 57 W/(m×К) characteristic of metal in the mass of thermoplastic rubber, which increases the total thermal conductivity of the mass in the reactor by up to 70 times to 12.7 W/(m∙K) due to the introduction of high thermal conductivity of metal bead rings. The resulting values of thermal conductivity of the mass of whole tires in the pyrolysis reactor at the optimum arrangement of raw materials and coefficient of filling about 98 % allow optimizing the structural characteristics of the pyrolysis equipment, thus confirming the prospects of the proposed modern technology of whole tire pyrolysis under the action of two factors – temperature and mechanical compression. The development of high-performance series industrial equipment for thermal recycling of tires with full process automation and production of alternative liquid fuels according to this technology is planned.